Socio-cultural aspect of digital transformation of society: analyses of main theories - Saltanovich, Irуna P. (Journal of the Belarusian State University. Sociology, 2025)
The impact of digital technologies on socio-cultural processes is analysed. Key theories that explain changes in social interactions, cultural practices and identities due to digitalisation are described. The article focused on the transformation of cultural norms and values, the creation of new forms of communication through technology and how technology facilitates the emergence of new communities and identities. Challenges and opportunities arising from digital transfor mation, as well as their impact on social inequalities and cultural diversity are identified. The relationship between the dynamic development of information and communication technologies and socio-cultural transformations is examined from an interdisciplinary perspective. The need to rethink the relationship between science and technology within a distributed theoretical framework is emphasised as an important factor for further discussion of the transdisciplinary nature of digital transformation. The task of socio-cultural modelling of the «global present» is addressed through the analysis of theories about some aspects of digital transformations of society and culture. The results of the study may be useful for scholars and practitioners interested in considering the socio-cultural implications of the digital age and in developing new approaches to the study and management of technology.
Keywords: digital transformation; culture; theories; technological determinism; media wealth; digital dividend; digital disruption